2022
DOI: 10.6118/jmm.22020
|View full text |Cite
|
Sign up to set email alerts
|

Labial Adhesion Secondary to Lichen Sclerosus Masked by Vulvar Hailey–Hailey Disease

Abstract: Labial adhesions in postmenopausal women are caused by various inflammatory processes in the context of estrogen deficiency. Lichen sclerosus (LS) is a chronic, progressive condition characterized by idiopathic epithelial thinning of the anogenital region with symptoms of significant pruritus, discomfort, and dyspareunia. Early diagnosis and treatment of LS can prevent disease progression, leading to labial adhesions and malignancy. We present an 84-year-old woman with long-standing vulvar Hailey–Hailey diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The exact mechanism of VLS development is not fully understood, but most scholars believe that its formation is implicated in immune system abnormalities, estrogenic changes, and genetic factors of patients ( 13 ). Research has indicated that in patients with VLS, the cellular immune responses, including T-lymphocyte-mediated autoimmune responses, may be abnormal, giving rise to lesions induced by damage to tissues and inflammatory responses ( 14 ). VLS may also be induced by immune abnormalities due to autoimmune diseases, such as autoimmune thyroid diseases and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of VLS development is not fully understood, but most scholars believe that its formation is implicated in immune system abnormalities, estrogenic changes, and genetic factors of patients ( 13 ). Research has indicated that in patients with VLS, the cellular immune responses, including T-lymphocyte-mediated autoimmune responses, may be abnormal, giving rise to lesions induced by damage to tissues and inflammatory responses ( 14 ). VLS may also be induced by immune abnormalities due to autoimmune diseases, such as autoimmune thyroid diseases and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%